Study of Effects of Hot Phonon on Hot Electron Transport (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
We study the influence of hot phonons on hot electron transport within the drain region is investigated. The ensemble Monte Carlo (MC) method self-consistently coupled with Poisson's equation is used. This MC simulation is three-dimensional in k-space and two-dimensional in real space. The two-dimensional model is possible if physical quantities have no significant variation along the third direction. The phonon Boltzmann transport equation (BTE) is solved and the mean heat generation rate is calculated.
Keywords: Hot electron; Monte Carlo simulation; Phonon population